Rancang Bangun Water Change Otomatis Berdasarkan Kekeruhan Air pada Aquarium dengan Penerapan Internet of Things (IoT) Berbasis Android - Wahjudi, Dodi; Watiningsih, Tri; Adynata, Pandega; Sukowati, Irawan Dharma (Proceedings Series on Physical & Formal Sciences, 2023)
Recently, maintaining ornamental fish has become a hobby in society, from the lower classes to the upper classes. Draining and filling water in the existing aquarium is still done manually. Many people like to keep fish confused if they travel far. No one may maintain fish properly. So, worrying about regular water changes. An important factor in keeping fish is the level of turbidity of the water. The turbidity level of water that can be tolerated by warm water fish is 25NTU (Nephelometric Turbidity Unit). So based on the above considerations, the researcher tried to submit a research proposal with the title "Design of Automatic Water Change Based on Water Turbidity in Aquariums with the Application of Android-Based Internet of Things (IoT). The developed system is expected to be able to maintain the level of water turbidity and replace water automatically in the aquarium so that it can increase the life expectancy of fish. The results of this study are that this system can effectively reduce the turbidity value of water in the aquarium. After being tested 10 times the system can keep the water turbidity level below the value that can be tolerated by warm water fish (25NTU).